To Manipulate or Not? Management of Pediatric Knee Arthrofibrosis Following Operative Fixation of Tibial Spine Fractures - Matthew J. Folkman, BS; Neeraj M. Patel, MD, MPH, MBS; Alexandra C. Stevens, BS; Aristides I. Cruz, Jr, MD; R. Jay Lee, MD; Indranil Kushare, MD; Theodore J. Ganley, MD; Henry Ellis, MD; Peter Fabricant, MD; Daniel Green, MD, MS; Benjamin Johnson, PA-C; Scott Mckay, MD; et al. (Elsevier, 2024)
Background: Knee arthrofibrosis is a common complication after surgical fixation of tibial spine fractures. However, there is no standardized treatment modality for resultant arthrofibrosis, with some surgeons electing for nonoperative management, while others prefer manipulation under anesthesia with a possible arthroscopic lysis of adhesions, if indicated. To better understand indications and outcomes from these treatment modalities for arthrofibrosis, we examined patients treated by both approaches. Methods: We performed a multicenter retrospective case series of patients with arthrofibrosis after tibial spine fracture surgery. Arthrofibrosis was defined as loss of knee extension ≥10.0° and/or knee flexion ≥25.0° compared to the contralateral, uninjured knee at three months following index surgery. Patients were organized into 2 cohorts: nonoperative and operative treatment. Data were collected for demographics, fracture classification, concomitant injuries, treatment timeline, and knee range of motion. Results: There were 16 patients in the operative group and 10 patients in the nonoperative group. At the time of diagnosis, the operative group had a mean 10° larger flexion deficit compared to the nonoperative group. Both treatment modalities resulted in similar ranges of motion at terminal evaluation. Final flexion was recorded as 130° in the operative group and 127° in the nonoperative group. Final extension deficits were 3° in both cohorts. Conclusions: Operative and nonoperative treatment modalities can be effective in management of knee arthrofibrosis after fixation of tibial spine fractures. Nonoperative treatment may be more suitable for milder range of motion deficits, but further research is necessary to guide clinical practice. Key Concepts: (1) Cohorts were similar in demographics, fracture classification, and concomitant injuries. (2) Patients who received a second operation presented with a greater flexion deficit. (3) The mean time between initial surgery and reoperation was 85 days. (4) Operative and nonoperative treatment of arthrofibrosis resulted in similar outcomes. Level of Evidence: Level IV, Case Series